ILLEGAL LAND GRAB: ISRAEL'S SEIZURE OF LAND IN PALESTINE - Saleh Raed Shatat; Ong Argo Victoria (Jurnal Akta, 2021)
Since 1967, each Israeli government has invested significant resources in establishing and expanding the settlements in the Occupied Territories, both in terms of the area of land they occupy and in terms of population. As a result of this policy, approximately 380,000 Israeli citizens now live on the settlements on the West Bank, including those established in East Jerusalem (this report does not relate to the settlements in the Gaza Strip). During the first decade following the occupation, the Ma'arach governments operated on the basis of the Alon Plan, which advocated the establishment of settlements in areas perceived as having "security importance," and where the Palestinian population was sparse (the Jordan Valley, parts of the Hebron Mountains and Greater Jerusalem). After the Likud came to power in 1977, the government began to establish settlements throughout the West Bank, particularly in areas close to the main Palestinian population centers along the central mountain ridge and in western Samaria. This policy was based on both security and ideological considerations. The political process between Israel and the Palestinians did not impede settlement activities, which continued under the Labor government of Yitzhak Rabin (1992-1996) and all subsequent governments. These governments built thousands of new housing units, claiming that this was necessary to meet the "natural growth" of the existing population. As a result, between 1993 and 2000 the number of settlers on the West Bank (excluding East Jerusalem) increased by almost 100 percent.